ANALISIS VALUE ADDED SEBAGAI INDIKATOR INTELLECTUAL CAPITAL TERHADAP KINERJA PERBANKAN DI INDONESIA - Heriaman Harianja (Ekonomi dan Keuangan, 2014)
The purpose of this research is to analyse the role of value added (VA) that human capital (VAHU), structural capital (STVA) and capital employed (VACA) as an indicator of Intellectual Capital. The data that was used in this research was the secondary data those are taken from the website www.idx.co.id obtained from annual reports of banking companies listen in Indonesia Stock Exchange.The sample selection is using purposive sampling method. The sample in this research is a conventional commercial bank listed in Indonesia Stock Exchange during the years 2010-2012 for 28 companies. Tests using the statistical data processing software is Eviews 6.0.The results of this research indicate that the value added of human capital (VAHU), structural capital value added (STVA) and value added capital employed (VACA) significant effect on financial performance (ROA), economic performance (OPM) and stock market performance (MBV) on Indonesian banking companies.Key words: Banking, Intellectual Capital, VAICTM, VAHU, STVA, VACA, ROA, OPM dan MBV.